SYNTHESIS AND CHARACTERIZATION OF TiO2/α-Fe2O3 COMPOSITE USING HEMATITE FROM IRON SAND FOR PHOTODEGRADATION REMOVAL OF DYE - Surya Lubis; Ilham Maulana; Masyithah . (Universitas Syiah Kuala, 2018)
In this paper, TiO2/α-Fe2O3 composite with high photocatalytic activity was prepared by a mechanical milling using iron sand from Lampanah in Aceh Besar regency as hematite (α-Fe2O3) source. Hematite was extracted from iron sand by using hydrochloric acid followed by co-precipitating using ammonium hydroxide as co-precipitation agent. Hematite and TiO2 powder were mixed and milled on a planetary ball mill without incorporating any solvent. The materials were characterized by using X-ray difraction (XRD) and scanning electron microscopy energy dispersive x-ray spectroscopy (SEM-EDX). The XRD results showed that the iron (III) oxide synthesized was hematite (α-Fe2O3) phase with the average crystallite size 27.967 nm. SEM analysis showed that iron sand was on irregular form, while the hematite (α-Fe2O3) and TiO2/α-Fe2O3 composite was on regular sphere. The TiO2/α-Fe2O3 composite was evaluated on photodegradation of indigo carmine (IC) dye using UV light irradiation. The highest degradation efficiency of IC (100%) was obtained by initial pH of dye solution equal to 1, photocatalyst dosage of 0.2 g, initial dye consentration of 5 mg/L for 120 min irradiation time. The photocatalytic activity of TiO2/α-Fe2O3 composites using UV light was almost the same as that of by solar light. Keywords: Iron sand, α-Fe2O3/TiO2 composite, mechanical milling, photocatalyst, indigo carmine